The Jurisdiction of the Prosecutor's Office is to Confiscate Assets and Eradicate the Crime of Money Laundering - Santoso, Prijo; Pujiono, Bambang (PT FORMOSA CENDEKIA GLOBAL, 2024)
Simply put, money laundering is the criminal act of transforming the proceeds of crimes, or what is known as